Analisis Rasio Likuiditas dan Profitablitas terhadap Kinerja Keuangan Pada PT Mega Perintis Tbk - Risaldy Al’Falaq (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
In this study,confirmation of the financial performance experienced by PT Mega Printis Tbk reflects a stable position and ia able to manage goog asset turnover in profitability and is able to manage short-term liability capitabilities well so that it is stated that PT Mega Perintis has good financial performance. The analytical tool used in this study is the multiple ratio analysis method, namely using liquidity and profitability ratios.